The Managerial Competence of Vocational High School Principals at SMKN 2 Luwu - Nurwahidah, Nurwahidah (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2025)
This study aims to analyze the managerial competence of the principal at SMKN 2 Luwu in managing vocational education. Managerial competence is a crucial factor that influences the effectiveness of school leadership, especially in vocational high schools that require practical and industry-oriented learning environments. The research employs a qualitative descriptive approach, collecting data through interviews, observations, and documentation. The findings indicate that the principal of SMKN 2 Luwu demonstrates adequate competence in planning, organizing, directing, and evaluating educational activities. However, certain challenges remain, such as limited industry collaboration and resource management constraints. The study concludes that enhancing managerial competence through continuous professional development and strategic partnerships with industry is essential for improving the quality of vocational education. This research contributes to a better understanding of leadership practices in vocational schools and offers recommendations for policy and practice improvement.